A pilot study to demonstrate the paracrine effect of equine, adult allogenic mesenchymal stem cells in vitro, with a potential for healing of experimentally-created, equine thoracic wounds in vivo - Caruso, Michael; Shuttle, Shannon; Amelse, Lisa; Elkhenany, Hoda; Schumacher, James; Dhar, Madhu S. (Frontiers in Veterinary Science, 2022)
Regenerative biological therapies using mesenchymal stem cells (MSCs) are being studied and used extensively in equine veterinary medicine. One of the important properties of MSCs is the cells’ reparative effect, which is brought about by paracrine signaling, which results in the release of biologically active molecules, which in turn, can affect cellular migration and proliferation, thus a huge potential in wound healing. The objective of the current study was to demonstrate the in vitro and in vivo potentials of equine allogenic bone marrow-derived MSCs for wound healing. Equine bone marrow-derived MSCs from one allogenic donor horse were used. Equine MSCs were previously characterized for their in vitro proliferation, expression of cluster-of-differentiation markers, and trilineage differentiation. MSCs were first evaluated for their migration using an in vitro wound healing scratch assay, and subsequently, the conditioned medium was evaluated for their effect on human fibroblast proliferation. Subsequently, allogenic cells were intradermally injected into full-thickness, cutaneous thoracic wounds of 4 horses. Wound healing was assessed by using 3-D digital imaging and by measuring mRNA expression of pro-and anti-inflammatory markers for 30 days. Using human fibroblasts in an in vitro wound healing assay, we demonstrate a significantly higher healing in the presence of conditioned medium collected from proliferating MSCs than in the presence of medium containing fetal bovine serum. Contrary to our expectation, the in vitro findings could not be translated into an in vivo equine model of cutaneous wound healing. Nonetheless, we proved that molecularly characterized equine allogenic MSCs do not illicit an immunologic response. Investigations using fat-derived MSCs and a compromised animal model are required to prove the efficacy of equine MSCs in wound healing in vivo.